Employer Branding as a Contemporary Challenge In the 2020 Workplace; During the Era of Transformational Change - Mostafa, Bassant (The Arab Journal of Administration, 2021)
Nowadays in the dynamic transformational environment, organizations face many challenges to become more knowledge-based, more emphasis on innovation and technology, as well as facing intensive competition for attracting and retaining a high-quality workforce. Those organizations seek employees from different cultural backgrounds and more attention is given to the “Generation Z” namely digital talents; entering the 2020 market place. So organizations should meet the previously mentioned challenges’ by differentiating themselves from other competitors in the labor market and enhancing their employer attractiveness as a tool to ensure competitive advantage for the organizations. This research aims at getting a clearer understanding of Generation Z perception of 2020 workplace and reflecting on how an employer branding (EB) strategy can be the answer for differentiation, through the delivery of a value proposition based on functional, symbolic and economical benefits, which should be consistent with the needs of this new generation. To carry out this mission, employers need to have a strong and unique value proposition and, at the same time, need to know how to communicate this value to potential candidates (Generation Z) using digital codes and channels. Generation Z is represented in this research by undergraduate students who are in their final year of study, selected from British University in Egypt. The practical implication of this research should suggest the appropriate employer branding strategies and identify the relevant set of responsibilities required for organizations taking strategic steps toward “the war for talent.”